Pengaruh Diskriminasi Harga Terhadap Stabilitas Persaingan Usaha Di Indonesia - Zaky Raihan; Karim Karim; Novita Rahmasari; Darul Arqom; Fitri Raya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The definition of price is the value of goods which is determined or expressed in terms of money or the amount of money or other equivalent means of exchange, which must be paid for goods or services, at a certain time and in a certain market. The price level attached to the product describes the quality of the product. Meanwhile, price discrimination is a term used in international trade, referred to as a trade practice carried out by exporters by selling every commodity on the international market at a price that is less than the appropriate value or can be said to be lower than the price of the goods in their own country, which is considered unfair because can damage the market and harm competing producers in the importing country. Among the activities of entrepreneurs that usually do not favor competition is price discrimination. This situation describes a situation where sellers provide different prices for their products with the same quality and quantity to two or more sellers, or provide unequal prices to buyers or consumers in the form of inappropriate inventory, or take action by setting a pricing strategy. to gain advantages for more profitable consumers.